Islam Salafi, Tafsir, dan Politik Penyuntingan - Sunarwoto, Sunarwoto (Lajnah Pentashihan Mushaf Al-Qur'an, 2024)
Traditionalists have strongly criticized that the ambition to refer to the Qur’an and sunnah led Salafis to disconnect the intellectual network (isnad) of Islam from the prophet Muhammad. However, a meticulous reading demonstrates that Salafis are far from ignoring the Islamic intellectual heritage of the past produced after the periods of three early generations of Islam (al-salaf). This can be seen in the Salafi scholarly production by editing (tahqiq) and publishing classical Islamic texts. This article is to study Mufradat Alfaz Al-Qur’an (MAQ) by ar-Ragib al-Asfihaniy (d. 1108) edited by Mustafa al-’Adawiy. It aims to elaborate on how Salafi scholarly production has been developed. Methodologically, it utilizes Gerard Genette’s paratextual model. It is argued that the editing of MAQ by al-’Adawiy is an attempt to claim the connection of Salafi Islam with the Islamic intellectual tradition in the past. Moreover, al-’Adawiy’s editing generates a typically Salafi-oriented interpretation, which corrects previous interpretations. This is a kind of “politics of editing.”